2019
DOI: 10.1016/j.sjbs.2018.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Decolorization and detoxification of textile dyes using a versatile Streptomyces laccase-natural mediator system

Abstract: Currently, there is increasing interest in assessing the potential of bacterial laccases for industrial and environmental applications especially in harsh conditions. The environmental impact of the textile industry requires novel and effective technologies to mitigate the presence of dyes in wastewaters before discharging into the environment. Dyes usually remain stable in the presence of a variety of chemicals, light and are recalcitrant to microbial degradation. Among available technologies the biological t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(50 citation statements)
references
References 35 publications
2
48
0
Order By: Relevance
“…Laccase is abundant in nature and sustainable. Besides, it is available in sufficient quantities and robust enough to be used in numerous industrial processes, e.g., in the food industry for processing and stabilizing beverages and additives in baking [ 25 , 26 ], for decolourisation and degradation of dyes in the textile industry, for pollution control in water and soil [ 17 , 27 , 28 , 29 , 30 ] as well as for pulp bleaching in the pulp and paper industry [ 24 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Laccase is abundant in nature and sustainable. Besides, it is available in sufficient quantities and robust enough to be used in numerous industrial processes, e.g., in the food industry for processing and stabilizing beverages and additives in baking [ 25 , 26 ], for decolourisation and degradation of dyes in the textile industry, for pollution control in water and soil [ 17 , 27 , 28 , 29 , 30 ] as well as for pulp bleaching in the pulp and paper industry [ 24 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…e oxidized radical form of the SA is able to oxidize a wide range of substrates, including compounds with a high redox and/or nonphenolic compound. Previous research has reported that phenolic compounds related to lignin have shown their capability and efficiency to act as Journal of Chemistry natural Lac mediators [37]. Although ABTS and HBT are well-known arti cial redox mediators for Lac, these mediators are not economically feasible.…”
Section: Catalyticmentioning
confidence: 99%
“…Metal ions such as Cu +2 , Ca +2 , Ni +2 , Co +2 , and Mn +2 are generally known to accelerate laccase activity at a remarkable level [13].Due to broad substrate spectrum, laccases have become very attractive for a variety of biotechnological and industrial applications such as organic synthesis; lignin degradation; and bio-product formation for the food, textile, and pharmaceutical industries; remediation of contaminated environments; as well as construction of biosensors and biofuel cells [14][15][16]. During the last decade laccases have been used in decolorization and detoxification of textile effluents [17]. Effluents from the textile industry are usually complex, containing a wide variety of synthetic dyes [18], among which the most common are azo dyes, anthraquinone, triphenylmethane, and indigo dyes [19].In the recent years, development of high-performance recombinant bacterial strains and the possibility of increasing the production of recombinant proteins created new opportunities for the commercial use of laccases, since the production from wild type strains has limitations in growth and product yield, which are not suitable for standard industrial fermentations [20].…”
mentioning
confidence: 99%
“…Due to broad substrate spectrum, laccases have become very attractive for a variety of biotechnological and industrial applications such as organic synthesis; lignin degradation; and bio-product formation for the food, textile, and pharmaceutical industries; remediation of contaminated environments; as well as construction of biosensors and biofuel cells [14][15][16]. During the last decade laccases have been used in decolorization and detoxification of textile effluents [17]. Effluents from the textile industry are usually complex, containing a wide variety of synthetic dyes [18], among which the most common are azo dyes, anthraquinone, triphenylmethane, and indigo dyes [19].…”
mentioning
confidence: 99%